PENELUSURAN SENYAWA SITOTOKSIK PADA KULIT BIJI NYAMPLUNG (Calophyllum inophyllum L.) DAN KEMUNGKINAN KORELASINYA SEBAGAI ANTIKANKER - Santi, Sri Rahayu (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification of active toxic compounds from nyamplung skin bean (Calophyllum inophyllum L). has been carried out. As much as 12,43 g of concentrated methanol extract was resulted from 1.0 kg dry powder nyamplung skin bean that was macerated using methanol. This extract was dissolved into methanol-water (7:3) and then partitioned with n-hexane and chloroform respectively. The result of toxicity test to both extract showed that chloroform extract was the most active toxic with LC50 = 239,88 ppm Separation of chloroform extract using preparative thin layer chromatography (TLC) resulted in F5 fractions that was white yellowish as much as 52 mg and LC50 = 151,36 ppm. Infra red and UV-vis spectroscopy were employed in order to identify the F5 fraction. The result of identification showed that isolate was aldehide triterpenoide compounds which had functional group like –OH (3429 cm-1), -CH aldehyde (2922,9 and 2852,9 cm-1), -CºC- (2360 cm-1), -C=O (1742,7 cm-1), -C=C- alkene(1637,0 cm-1), -CH3, -CH2 (1542,9, 1480,7, 1401,9 cm-1), -CO- (1090 cm-1), It showed absorbed at broad peaks at l(nm) (CHCl3): 254, 282, and 342,7.
Keywords: Calophyllum inophyllum L., toxicity, isolation, identification